EFFECTS OF VITAMIN D ON MATRIX METALLOPROTEINASE 9 AND APOPTOSIS IN EXPERIMENTAL DIABETIC RAT KIDNEY TISSUE - Gozel, Nevzat; Genc, Fatih; Ozdemir, Fethi Ahmet; Kuloglu, Tuncay; Kaya, Nalan; Yalcin, Mehmet Hanifi; Donder, Emir (Parlar Scientific Publications (P S P), 2018)
Diabetic nephropathy is ranked first among diabetes related causes of death. Matrix metalloproteinases are enzymes that play a role in the breakdown and transformation of the extracellular matrix. The objective of this study was to examine the effects of vitamin D on Metalloproteinase 9 and apoptosis in the kidney tissue of experimental diabetic rats. Wistar albino male rats were used in the study. The animals used in the study were classified into 5 groups with 7 rats in each. No process was applied on the control group. Single dose phosphate citrate buffer was administered to the buffer group intraperitoneally, 50 IU/day vitamin D was administered to the vitamin D group, whereas single dose of 50 mg/kg streptozotosin was administered to the diabetes group and single dose of 50 mg/kg streptozotosin was administered to the diabetes + vitamin D group thus resulting in diabetes after which vitamin D was administered as 50 IU/day. Immunohistochemical staining was applied for determining the metalloproteinase 9 levels, whereas TUNEL labeling was applied for apoptosis. The biochemical total antioxidant status (TAS) and total oxidant status (TOS) levels of the samples were determined. Apoptosis, TAS, TOS, and metalloproteinase 9 values were similar in the control, buffer and vitamin D groups. There was a decrease in the TAS values despite the increase observed when the TOS, apoptosis and metalloproteinase 9 values of the diabetes group were compared with the control group. Whereas a decrease was observed when the TOS, apoptosis and Metalloproteinase 9 values of the Diabetes + vitamin D group were compared with those of the diabetes group despite the increase in TAS values. We have demonstrated that treatment approaches related with vitamin D may be tried for decreasing diabetes related complications.
Keywords: Diabetes mellitus; Matrix metalloproteinase 9; apoptosis; vitamin D